Technological Advances to Address Current Issues in Entomology: 2020 Student Debates. Issue 2 (28th April 2021) - Bernaola, Lina; Darlington, Molly; Britt, Kadie; Prade, Patricia; Roth, Morgan; Pekarcik, Adrian; Boone, Michelle; Ricke, Dylan; Tran, Anh; King, Joanie; Carruthers, Kelly; Thompson, Morgan; et al.
Abstract: The 2020 Student Debates of the Entomological Society of America (ESA) were live-streamed during the Virtual Annual Meeting to debate current, prominent entomological issues of interest to members. The Student Debates Subcommittee of the National ESA Student Affairs Committee coordinated the student efforts throughout the year and hosted the live event. This year, four unbiased introductory speakers provided background for each debate topic while four multi-university teams were each assigned a debate topic under the theme 'Technological Advances to Address Current Issues in Entomology'. The two debate topics selected were as follows: 1) What is the best taxonomic approach to identify and classify insects? and 2) What is the best current technology to address the locust swarms worldwide? Unbiased introduction speakers and debate teams began preparing approximately six months before the live event. During the live event, teams shared their critical thinking and practiced communication skills by defending their positions on either taxonomical identification and classification of insects or managing the damaging outbreaks of locusts in crops.